Role of COX-2/mPGES-1/Prostaglandin E2 Cascade in Kidney Injury - Jia, Zhanjun (Mediators Inflamm, 2015)
COX-2/mPGES-1/PGE2 cascade plays critical roles in modulating many physiological and pathological actions in different organs. In the kidney, this cascade is of high importance in regulating fluid metabolism, blood pressure, and renal hemodynamics. Under some disease conditions, this cascade displays various actions in response to the different pathological insults. In the present review, the roles of this cascade in the pathogenesis of kidney injuries including diabetic and nondiabetic kidney diseases and acute kidney injuries were introduced and discussed. The new insights from this review not only increase the understanding of the pathological role of the COX-2/mPGES-1/PGE2 pathway in kidney injuries, but also shed new light on the innovation of the strategies for the treatment of kidney diseases.